CD57 Expression and Cytokine Production by T Cells in Lesional and Unaffected Skin from Patients with Psoriasis - Batista, Mariana D. (Public Library of Science, 2013)
BACKGROUND: The immunopathogenic mechanisms leading to psoriasis remain unresolved. CD57 is a marker of replicative inability and immunosenescence on CD8+ T cells and the proportion of CD57 expressing CD8+ T cells is increased in a number of inflammatory conditions. METHODOLOGY: We examined the expression of CD57 on T cells in the skin of patients affected with psoriasis, comparing lesional and unaffected skin. We also assessed functionality of the T cells by evaluating the secretion of several inflammatory cytokines (IL-17A, IFN-gamma, IL-2, IL-33, TNF-alpha, IL-21, IL-22, and IL-27), from cell-sorted purified CD4+ and CD8+ T cells isolated from lesional and unaffected skin biopsies of psoriasis patients. PRINCIPAL FINDINGS: We observed that the frequency of CD57+CD4+ and CD57+CD8+ T cells was significantly higher in unaffected skin of psoriasis patients compared to lesional skin. Sorted CD4+ T cells from psoriatic lesional skin produced higher levels of IL-17A, IL-22, and IFN-gamma compared to unaffected skin, while sorted CD8+ T cells from lesional skin produced higher levels of IL-17, IL-22, IFN-gamma, TNF-alpha, and IL-2 compared to unaffected skin. CONCLUSIONS/SIGNIFICANCE: These findings suggest that T cells in unaffected skin from psoriasis patients exhibit a phenotype compatible with replicative inability. As they have a lower replicative capacity, CD57+ T cells are less frequent in lesional tissue due to the high cellular turnover.